Acute upsurge of tumour markers in ruptured ovarian endometrioma: a false alarm for malignancy: a case report - Thomas, Deepika Theresa; Rani, G. Usha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
CA 125, in gynaecological practice, is seen to be elevated in both benign and malignant conditions. Higher values, usually raise the suspicion of malignancy. Here we report a case of a 21-year-old nulliparous female, with extremely high evels of CA 125, suspected malignancy, but laparoscopy revealed a ruptured ovarian endometrioma, which was confirmed by histopathology. We discuss the pathogenesis of the same, evaluation and approach to management of ruptured endometriotic cysts.